2015
DOI: 10.1080/10888438.2015.1007375
|View full text |Cite
|
Sign up to set email alerts
|

Text (Oral) Reading Fluency as a Construct in Reading Development: An Investigation of Its Mediating Role for Children From Grades 1 to 4

Abstract: In the present study we investigated a developmentally changing role of text reading fluency in mediating the relations of word reading fluency and listening comprehension to reading comprehension. We addressed this question by using longitudinal data from Grades 1 to 4, and employing structural equation models. Results showed that the role of text reading fluency changes over time as children’s reading proficiency develops. In the beginning phase of reading development (Grade 1), text reading fluency was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
116
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 50 publications
14
116
0
13
Order By: Relevance
“…Much evidence has provided support for the simple view of reading in several languages (Catts, Adlof, & Ellis Weismer, 2006 ;Johnston & Kirby, 2006 ;Joshi & Aaron, 2000 ;Joshi, Tao, Aaron, & Quiroz, 2012 ;Kendeou, van den Broek, White, & Lynch, 2009 ;Kim, 2015 ;Protopapas, Mousaki, Sideridis, Kotsolakou, & Simos, 2013 ), and showed that oral language skills such as vocabulary and listening comprehension are critical for reading comprehension, and their importance increases as children develop reading skills (Foorman, Koon, Petscher, Mitchell, & Truckenmiller, in press ;Kim & Wagner, 2015 ;Kim, Wagner, & Lopez, 2012 ). Despite its recognized importance, however, what it takes to develop listening comprehension has been nebulous, which is in stark contrast to our understanding about skills that contribute to word reading (see Adams, 1990 ;Bowey, 2005 ;National Early Literacy Panel, 2008 ).…”
Section: Why Listening Comprehension For Reading and Writingmentioning
confidence: 99%
“…Much evidence has provided support for the simple view of reading in several languages (Catts, Adlof, & Ellis Weismer, 2006 ;Johnston & Kirby, 2006 ;Joshi & Aaron, 2000 ;Joshi, Tao, Aaron, & Quiroz, 2012 ;Kendeou, van den Broek, White, & Lynch, 2009 ;Kim, 2015 ;Protopapas, Mousaki, Sideridis, Kotsolakou, & Simos, 2013 ), and showed that oral language skills such as vocabulary and listening comprehension are critical for reading comprehension, and their importance increases as children develop reading skills (Foorman, Koon, Petscher, Mitchell, & Truckenmiller, in press ;Kim & Wagner, 2015 ;Kim, Wagner, & Lopez, 2012 ). Despite its recognized importance, however, what it takes to develop listening comprehension has been nebulous, which is in stark contrast to our understanding about skills that contribute to word reading (see Adams, 1990 ;Bowey, 2005 ;National Early Literacy Panel, 2008 ).…”
Section: Why Listening Comprehension For Reading and Writingmentioning
confidence: 99%
“…For adults, recognizing the same words out of context may be different than recognizing words in context. Future studies on text reading fluency would be informative to reveal struggling adult readers' text processing (e.g., see Kim & Wagner, 2015 for the role of text reading fluency in reading comprehension over and above word reading and language comprehension; see also for adults). Research has consistently indicated that reading fluency (Fuchs et al, 2001;Klauda, & Guthrie, 2008 regarding children; see Rasinski et al, 2005 for adults).…”
Section: Discussionmentioning
confidence: 99%
“…As individuals become skilled readers, they learn to construe meanings, make connections, and infer meaning beyond the cursory interpretation. With text experience and automaticity, the influence of word reading on reading comprehension decreases and other skills such as language comprehension and vocabulary become more important (Hoover & Gough, 1990;Kim & Wagner, 2015;Mellard & Fall, 2012). Beginning readers rely heavily on decoding processes in order to decipher the written code and translate it into phonological representation.…”
Section: Reading Component Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ler envolve o reconhecimento de palavras, a compreensão da linguagem (Kim & Wagner, 2015), além de processar os aspectos gráficos do texto, integrá-los com aspectos sintáticos, semânticos e o conhecimento de mundo. Pensar num modelo teórico que explique a compreensão de leitura é um desafio para pesquisadores (Florit & Cain, 2011).…”
unclassified